Sustainability assessment : criteria and processes - Gibson, Robert B., 1950- (Earthscan, 2005)
This work tackles the complexities of sustainability assessment and provides practical solutions and comprehensive analysis, guidance and criteria for impact assessment professionals and policy makers at all levels and in all circumstances.
Keywords: Sustainable development.; Economic development -- Environmental aspects.; Développement durable.; Développement économique -- Aspect de l'environnement.; sustainable development.; BUSINESS & ECONOMICS -- Development -- Sustainable Development.; BUSINESS & ECONOMICS -- Environmental Economics.; Economic development -- Environmental aspects; Sustainable development; Nachhaltigkeit; Bewertung; Desenvolvimento sustentável.